Bioefficacy of Andrographis paniculata (Burm. F.) Nees Against Meloidogyne incognita in Okra, Abelmoschus esculentus (L) Moench (Indian Journal of Nematology, 2024)
The efficacy of solvent (acetonitrile, acetone, methanol and water) extracted powder of Andrographis paniculata was studied in vitro at different concentrations (1, 5, 10 and 15%) on the egg hatching and juvenile mortality of Meloidogyne incognita, and further in a pot experiment in okra plants. Methanol extract at 15% exhibited the lowest egg hatching (0 to 1.18%) after an exposure period of three to eight days and juvenile mortality of 92 to 99.33% at 24 to 72 hrs. Based on the results of this study, an oil-based formulation of A. paniculata was prepared by mixing the methanol-extracted dried powder in pongamia oil and Polysorbate80. Different concentrations (0.5, 1, 2, 2.5 and 5%) of the oil-based formulation were tested in vitro on the egg hatching and juvenile mortality of M. incognita. Oil-based formulation of A. paniculata (5%) was effective in inhibiting egg hatching (97.19 to 99.49%) at three to eight days after treatment and showed a significant effect on juvenile mortality (82.67 to 99.33%) 24 to 72 hrs after treatment. Soil drenching of oil-based formulation of A. paniculata (10%) in the rhizosphere of okra plants under pot culture conditions significantly suppressed the nematode population in soil (80.47%) and increased the fruit yield (89.37%).